A obesidade abdominal dinapênica acelera o declínio da mobilidade e da função de membros inferiores em pessoas idosas? - Máximo, Roberta de Oliveira (Universidade Federal de São Carlos, 2022)
The decline in mobility and lower extremity function are considered the sixth vital sign in older people, as they are precursors of functional disability and predictors of adverse outcomes such as hospitalization, early institutionalization, and death. Although multifactorial in nature, it is affected by two common and gender-differentiated processes in aging: abdominal obesity and dynapenia. However, there is still little evidence on the effect of dynapenic abdominal obesity on the decline in physical performance over time. Thus, the present proposal aims to: 1) analyse the effect of dynapenic abdominal obesity on the trajectory of mobility decline in 2,294 individuals aged 60 years or older, free of mobility limitation at baseline (gait speed > 0.8 m/ s), during eight years of follow-up; 2) analyse sex differences in the effect of dynapenic abdominal obesity on the trajectory of lower extremity function decline in 3,875 individuals aged 60 years or older during eight years of follow-up. The data come from the English Longitudinal Study of Aging (ELSA) having as a baseline the information obtained in the year 2004 that was repeated in four and eight years of follow-up. Mobility was assessed by gait speed (m/s) and lower extremity function by the Short Physical Performance Battery (SPPB). Abdominal obesity was defined for waist circumference values > 102 cm for men and > 88 cm for women and dynapenia was considered for values of handgrip strength < 26 kg for men and < 16 kg for women. Participants were classified as non-dynapenic/non-abdominal obesity (ND/NAO); non-dynapenic/abdominal obesity (ND/AO); dynapenic/non-abdominal obesity (D/NAO) and dynapenic abdominal obese (D/AO). Generalized linear mixed models adjusted for sociodemographic, lifestyle, neuropsychiatric, and health status factors were used to trace different trajectories of lower extremity mobility and function decline over eight years of follow-up for each of the four groups analysed. The main results of the longitudinal study carried out with 2,294 subjects aged 60 years or older free from mobility limitation at baseline (gait speed > 0.8 m/s) demonstrate that over eight years of follow-up only D/AO subjects had a greater decline in gait speed (-0.013 m/s per year 95% CI: -0.024 – -0.002; p < 0.05) compared to ND/NAO. The main results of the longitudinal analysis performed with 3,875 older people showed that, at the beginning of the study, men (-1.11 points; 95% CI: -1.58 – -0.65; p < 0.001) and women (-1.39 points; 95% CI: -1.76 – -1.02; p < 0.001) the D/AO had the worst performances in the SPPB compared to their counterparts in the ND/NAO group. During the eight years of follow-up, only D/AO men had a faster decline in SPPB performance compared to ND/NAO men (-0.11 points per year; 95% CI: -0.21 – -0.01; p = 0.032). In conclusion, dynapenic abdominal obesity is associated with an accelerated decline in gait speed in older people of either sex and an accelerated decline in SPPB in men, but not in women. The results of this thesis highlight the importance of the clinical entity of dynapenic abdominal obesity as a very robust indicator to identify and monitor the risk of lower limb mobility and function decline in older people and indicate that efforts should focus on strategies to minimize its It is made. As we have seen, dynapenic abdominal obesity can occur as age advances, but it is potentially modifiable and, when neglected, has important repercussions on functional status, especially in men. The most current guidelines from the World Health Organization establish a policy for older people to incorporate a variety of aerobic exercises and muscle-strengthening activities into their routine. Equally important, public health initiatives need to be sufficient to allow early identification of the dynapenic abdominal obesity phenotype, so that its proper management can prevent the first signs of impaired physical performance in older people.
Does dynapenic abdominal obesity accelerate the decline in mobility and lower extremity function in older people?
Keywords: Circunferência de cintura; Obesidade; Força de preensão manual; Dinapenia; Desempenho físico; Trajetórias; Waist circumference; Obesity; Handgrip strength; Dynapenia; Physical performance; Trajectories; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL